2022
DOI: 10.1111/dme.15013
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and early‐onset diabetes in Ukraine: Atypical features and mortality

Abstract: Aims:The aim of this study is to elucidate the aetiology and clinical features of neonatal and early-onset diabetes in a large database for pediatric diabetes patients in Ukraine. Methods:We established a Pediatric Diabetes Register to identify patients diagnosed with diabetes before 9 months of age. Genetic testing was undertaken for 66 patients from 65 unrelated families with diabetes diagnosed within the first 6 months of life (neonatal diabetes, n = 36) or between 6 and 9 months (earlyonset diabetes, n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The study cohort comprises 159 individuals identified through a systematic literature search from 62 studies 4,5,7,17–75 (Figure 1) and an additional 30 individuals who were collected via contacting physicians and study authors (Supplemental Table S1). Additional follow‐up data were acquired on 11 individuals already reported 7,24–26,28,45 via direct contact with the original study authors.…”
Section: Resultsmentioning
confidence: 99%
“…The study cohort comprises 159 individuals identified through a systematic literature search from 62 studies 4,5,7,17–75 (Figure 1) and an additional 30 individuals who were collected via contacting physicians and study authors (Supplemental Table S1). Additional follow‐up data were acquired on 11 individuals already reported 7,24–26,28,45 via direct contact with the original study authors.…”
Section: Resultsmentioning
confidence: 99%